Distant ruptures a selection of comics 2000-2010 - C. F. 1979- (NYRC, 2024)
"Pulling from pulp, sci-fi, gag cartoons, fantasy, and thrillers, and populated by goblins, astronauts, magical thieves, and talking owls, CF's comics break apart genres and forms, then reassemble them into one-of-a-kind stories that reveal an immense imagination and boundary-pushing talent. Christopher Forgues (better known as CF) roared onto the indie comics scene in the early 2000s, producing some of the most exciting and influential work of the decade. His output was startlingly original and impressively prolific: his collaboration with Ben Jones, Paper Radio; his multi-part epic, Powr Mastrs; and the shorter comics and zines now collected for the first time in Distant Ruptures. These comics--created using scratchy pencil and brilliant color, smudged Xeroxes and scraps of notepaper--capture the extraordinary range of CF's work. Fellow cartoonist Sammy Harkham has gathered the best of them into this new collection, which also includes an introduction by Gabriel Winslow-Yost and a new interview with CF. Distant Ruptures offers readers their first chance to see the full scope of this remarkable era of CF's comics."--
Keywords: Comic books, strips, etc; Comics (Graphic works); Bandes dessinées; Comic